Is flushing necessary during building closures? A study of water quality and bacterial communities during extended reductions in building occupancy - Greenwald, Hannah; Kennedy, Lauren C.; Ehde, Aliya; Duan, Yanghua; Olivares, Christopher I.; Kantor, Rose; Nelson, Kara L. (Frontiers in Water, 2022)
Drinking water stagnation can lead to degradation of chlorine residual, bacterial growth (including of opportunistic pathogens and nitrifiers), and metals release from plumbing materials; however, few studies have characterized building water quality and bacterial communities during the extended stagnation periods that occurred during COVID-19 pandemic-related building closures. Additionally, despite a lack of evidence-based guidance, flushing fixtures has been recommended to restore building water quality. We aimed to evaluate the impacts of reduced building occupancy (>2 months) and weekly restorative flushing on drinking water quality, bacterial communities, and the occurrence of undesirable microorganisms in three university buildings. Reduced occupancy led to diminished chloramine and elevated intact cell counts, but values remained stable after additional weeks of limited water use. Flushing temporarily improved water quality, with chlorine and cell counts remaining stable for at least one day but returning to levels measured prior to flushing within one week. Alpha diversity was lower under more stagnant conditions, and fixture identity, not flushing, was the most influential factor on bacterial community composition, suggesting a strong influence from local biofilm. Although Mycobacterium, Legionella, Pseudomonas, Nitrosomonas, and Nitrospira were detected in samples via amplicon sequencing, concentrations measured via qPCR of M. avium complex, L. pneumophila, P. aeruginosa, and ammonia-oxidizing bacteria were very low or were undetected, supporting that stagnation alone did not lead to high occurrence of undesirable microorganisms. Findings from this study contribute to our understanding of the effects of stagnation on building water microbiomes and the efficacy of flushing to improve water quality. Under the conditions of this case study, repeated flushing on a weekly timescale during low occupancy periods was not sufficient to maintain chlorine residual and prevent bacterial growth in fixtures. Building managers need to weigh the temporary water quality benefits of flushing against the labor and water resources required considering local context.